A kind of wear-resistant chenille yarn and its production process
Through the combination of modified polyester and carbon nanotubes and the finishing process of the modified finishing liquid, the problem of insufficient wear and flame retardant performance of existing Chenille yarns is solved, and higher wear and flame retardant performance is achieved, and the service life of the yarn is improved.
Patent Information
- Application Number
- CN202411887362.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-20
AI Technical Summary
The wear resistance and flame retardant properties of existing Chenilli yarns are insufficient, and their performance gradually decreases after long-term use.
Modified polyester is used as raw material, Chenille yarn is twisted by melt spinning and Chenille spinning machine, and the modified finishing solution is used for two-thickness and two-rolling method to form an inorganic-organic network with carbon nanotubes as the crosslinking point, improving the wear resistance and flame retardant properties of the yarn.
The wear resistance and flame retardant properties of Chenilli yarn are significantly improved, so that it can maintain good performance after long-term use, and reduce the performance degradation after washing.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of yarns, and in particular to a wear-resistant chenille yarn and a production process thereof. Background Art
[0002] Chenille yarn is a new type of fancy yarn. It is made of two strands of yarn as the core thread, and the feather yarn is sandwiched in the middle by twisting. Textiles with chenille yarn as the main raw material have the characteristics of full fiber, thick fabric and light texture. It has the advantages of high skin-friendliness and exquisite appearance. It is widely used in home textiles and knitted clothing.
[0003] At present, the commonly used raw material for chenille yarn is polyester fiber. However, polyester fiber is prone to pilling during daily use, resulting in poor wear resistance of the chenille yarn produced, which cannot meet the use requirements. At the same time, since the limiting oxygen index of polyester fiber is only 19%-22%, it is a flammable fiber. At the same time, the temperature difference between the melting point and the ignition point of polyester fiber is large. After being heated, the fiber softens, shrinks, and melts and drips before thermal decomposition. The highest combustion temperature during combustion can reach 690°C. Therefore, the chenille yarn obtained by spinning polyester fibers releases a lot of heat during the combustion process and burns violently. The large amount of molten droplets produced can easily cause secondary fires, posing a safety hazard. Summary of the invention
[0004] The purpose of the present invention is to provide a wear-resistant chenille yarn and a production process thereof, which solves the problem of insufficient wear resistance and insufficient flame retardancy of the existing chenille yarn, and can still maintain good wear resistance and flame retardancy after long-term use.
[0005] The purpose of the present invention can be achieved by the following technical solution: A wear-resistant chenille yarn is prepared by the following steps:
[0006] Step S1: adding the modified polyester to a melt spinning machine, melt spinning, and obtaining the modified polyester filaments, and passing through a chenille spinning machine, using two modified polyester filaments as core yarns and six modified polyester filaments as decorative yarns, and sandwiching the decorative yarns between the two core yarns and twisting them in a spiral shape to obtain chenille yarns;
[0007] Step S2: Mixing a modified finishing agent, ethanol and water to prepare a modified finishing liquid, wherein the mass concentration of the modified finishing agent in the modified finishing liquid is 4-8 g / L, and the volume ratio of ethanol to water is 5:1. The chenille yarn is finished by a two-immersion and two-rolling method, wherein the chenille yarn is immersed in the modified finishing liquid, the temperature of the two immersions is 30° C., the immersion time is 1 h, the bath ratio is 1:20, the rolling rate is 100%, and then pre-baking at 80° C. for 2 min and baking at 110° C. for 4 min to obtain the wear-resistant chenille yarn;
[0008] The modified polyester is prepared by the following steps:
[0009] Step A1: 2-allylcyclohexanone, m-chloroperbenzoic acid and dichloromethane are mixed, and the mixture is reacted for 20-24 hours at room temperature at a stirring rate of 240-300 rpm to obtain an intermediate M. The hydroxylated carbon nanotubes, the intermediate M and caprolactone are mixed and ultrasonically dispersed for 20 minutes, and then stirred under nitrogen protection at a stirring rate of 600-700 rpm and a temperature of 110° C., and stannous isooctanoate is added, and the mixture is reacted for 24 hours to obtain modified carbon nanotubes;
[0010] The ratio of 2-allylcyclohexanone to m-chloroperbenzoic acid is 0.03-0.04 mol: 0.05-0.06 mol, and the ratio of hydroxylated carbon nanotubes, intermediate M and caprolactone is 0.9-1 g: 0.03-0.04 mol: 0.08-0.1 mol;
[0011] During the reaction, the ketone bond in 2-allylcyclohexanone undergoes a Baeyer-Villiger reaction under the action of m-chloroperbenzoic acid, the ketone is oxidized to an ester to form a caprolactone structure, and the intermediate M and caprolactone are ring-opened under the action of stannous isooctanoate to react with the hydroxyl groups in the hydroxylated carbon nanotubes and polymerize to obtain modified carbon nanotubes.
[0012] Step A2: terephthalic acid, ethylene glycol, antimony trioxide and triphenyl phosphate are mixed, and the mixture is reacted for 1.5-2 hours under nitrogen protection, at a stirring rate of 500-600 rpm and a temperature of 220° C., and then pentaerythritol is added and the temperature is raised to 270° C., the system pressure is maintained at -0.09 MPa, and the reaction is carried out for 1 hour, and then modified carbon nanotubes and pyromellitic anhydride are added, and the reaction is continued for 1-1.5 hours to obtain a modified polyester;
[0013] The dosage ratio of terephthalic acid, ethylene glycol, antimony trioxide, triphenyl phosphate, pentaerythritol, modified carbon nanotubes and pyromellitic anhydride is 0.9-1 mol: 1.5-1.8 mol: 0.09-0.1 g: 0.1-0.12 g: 0.015-0.02 mol: 3-4 g: 0.015-0.02 mol;
[0014] During the reaction, under the action of antimony trioxide and triphenyl phosphate, the carboxyl group in terephthalic acid and the hydroxyl group in ethylene glycol were first esterified at 220°C, and then pentaerythritol was added under negative pressure and 270°C to undergo polycondensation with its hydroxyl group, and then pyromellitic anhydride and modified carbon nanotubes were added, and the anhydride in pyromellitic anhydride reacted with the hydroxyl group in the modified carbon nanotubes to form ester groups and carboxyl groups, and the carboxyl groups participated in the polycondensation process to obtain modified polyester.
[0015] The modified finishing agent is prepared by the following steps:
[0016] Step B1: Mix cyanuric chloride and acetone, stir at a rate of 240-300 rpm, and add p-nitrophenol and potassium hydroxide solution, and react for 1-2 hours to obtain intermediate a; mix 3-aminopropyltriethoxysilane, intermediate a and acetone, add saturated sodium carbonate solution to adjust the pH value to 9, and react for 4-6 hours under nitrogen protection, stirring at a rate of 240-300 rpm, and a temperature of 80°C to obtain intermediate b; mix intermediate b, palladium carbon catalyst and ethanol, and introduce hydrogen, and react for 6-8 hours at a stirring rate of 100-120 rpm and a temperature of 50°C to obtain intermediate c;
[0017] The molar concentration of the potassium hydroxide solution is 1 mol / L, the amount ratio of cyanuric chloride, p-nitrophenol and potassium hydroxide solution is 0.05 mol: 0.05-0.055 mol: 50-60 mL, the amount ratio of 3-aminopropyltriethoxysilane and intermediate a is 0.1-0.12 mol: 0.05 mol, and the amount ratio of intermediate b and palladium carbon catalyst is 0.05 mol: 0.8-1 g;
[0018] During the reaction, chlorine in cyanuric chloride undergoes a substitution reaction with phenolic hydroxyl in p-nitrophenol to obtain intermediate a, chlorine in intermediate a undergoes a substitution reaction with amino in 3-aminopropyltriethoxysilane to obtain intermediate b, and nitro in intermediate b is reduced to amino under the action of palladium-carbon catalyst to obtain intermediate c;
[0019] Step B2: 10-(2,5-dihydroxyphenyl)-10H-9-oxa-10-phosphaphenanthrene-10-oxide, epichlorohydrin, dichloromethane and deionized water are mixed, stirred at a stirring rate of 240-300 rpm and a temperature of 50° C., and sodium hydroxide is added to react for 8-10 hours to obtain intermediate d. Intermediate c, intermediate d and anhydrous ethanol are mixed, and the reaction is carried out at a stirring rate of 400-500 rpm and room temperature for 0.5-1 hour to obtain intermediate e;
[0020] The ratio of 10-(2,5-dihydroxyphenyl)-10H-9-oxa-10-phosphaphenanthrene-10-oxide, epichlorohydrin and sodium hydroxide is 0.01 mol: 0.02-0.024 mol: 4-5 g, and the ratio of intermediate c to intermediate d is 0.05 mol: 0.02-0.03 mol;
[0021] During the reaction, the phenolic hydroxyl group in 10-(2,5-dihydroxyphenyl)-10H-9-oxa-10-phosphaphenanthrene-10-oxide reacts with the epoxy group in epichlorohydrin to generate a hydroxyl group, and the hydroxyl group then reacts with chlorine under alkaline conditions to form an epoxy group, thereby obtaining an intermediate d containing an epoxy group, and the amino group in the intermediate c then reacts with the epoxy group in the intermediate d to form a hydroxyl group, thereby obtaining an intermediate e;
[0022] Step B3: Intermediate e, lipoic acid and dichloromethane are mixed, stirred at a rate of 200-240 rpm and room temperature in a dark environment, and 1-ethyl-(3-dimethylaminopropyl)carbodiimide, 4-dimethylaminopyridine and triethylamine are added, and the mixture is reacted for 24 hours to obtain a modified finishing agent;
[0023] The ratio of intermediate e, thioctic acid, 1-ethyl-(3-dimethylaminopropyl)carbodiimide, 4-dimethylaminopyridine and triethylamine is 0.02-0.03 mol: 0.05-0.06 mol: 0.08 mol: 0.08 mol: 0.12 mol;
[0024] During the reaction, under the action of 1-ethyl-(3-dimethylaminopropyl)carbodiimide, 4-dimethylaminopyridine and triethylamine, the carboxyl group in lipoic acid and the hydroxyl group in the intermediate e are esterified to obtain a modified finishing agent.
[0025] Beneficial effects of the invention: The invention discloses a wear-resistant chenille yarn and a production process thereof. Modified polyester is used as a raw material to prepare modified polyester filaments, and then the modified polyester filaments are used as a raw material to prepare chenille yarns, and modified finishing liquid is used to finish the chenille yarns to obtain the wear-resistant chenille yarns. Pentaerythritol is added in the preparation process of the modified polyester so that the modified polyester has a branched structure, and then pyromellitic anhydride and modified carbon nanotubes are added, so that the molecular chains of the modified carbon nanotubes and the modified polyester are connected by covalent bonds, and an inorganic-organic network with the carbon nanotubes as crosslinking points is constructed. Due to the high aspect ratio of the carbon nanotubes, when the modified polyester filaments are subjected to external forces, the stress is transferred from the matrix to the carbon nanotubes, thereby effectively improving the mechanical properties of the polyester filaments. Since the modified carbon nanotubes are obtained by grafting caprolactone with carbon nanotubes, the dispersion of the carbon nanotubes in the matrix is improved. Since the modified finishing agent is obtained by the reaction of thioctic acid and intermediate e, and since there is a disulfide bond in thioctic acid, during the double dipping and double rolling process of the chenille yarn, the disulfide bonds of the modified finishing agent are converted into thiol groups, a part of which undergoes self-crosslinking to reform the disulfide bonds, and the other part undergoes a click reaction with the double bonds in the modified carbon nanotubes to connect the modified finishing agent to the modified polyester filaments. In addition, since there is silicon ethoxy in the modified finishing agent, it undergoes hydrolysis and self-crosslinking. This crosslinking is combined with the crosslinking of the disulfide bonds, so that the modified finishing agent forms a coating on the surface of the modified polyester filaments, thereby improving the wear resistance of the chenille yarn. In addition, since the coating is connected to the modified polyester filaments by covalent bonds, it has good water wash resistance. Since the modified finishing liquid contains DOPO flame retardant groups and triazine flame retardant groups, it can form a phosphorus-nitrogen-silicon flame retardant system with silicon, so that the chenille yarn has good flame retardant properties. DETAILED DESCRIPTION
[0026] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0027] Example 1 A wear-resistant chenille yarn is prepared by the following steps:
[0028] Step S1: adding the modified polyester to a melt spinning machine, melt spinning, and obtaining the modified polyester filaments, and passing through a chenille spinning machine, using two modified polyester filaments as core yarns and six modified polyester filaments as decorative yarns, and sandwiching the decorative yarns between the two core yarns and twisting them in a spiral shape to obtain chenille yarns;
[0029] Step S2: Mixing a modified finishing agent, ethanol and water to prepare a modified finishing solution, wherein the mass concentration of the modified finishing agent in the modified finishing solution is 4 g / L, and the volume ratio of ethanol to water is 5:1. The chenille yarn is finished by a two-immersion and two-rolling method, wherein the chenille yarn is immersed in the modified finishing solution, the temperature of the two immersions is 30° C., the immersion time is 1 h, the bath ratio is 1:20, the rolling rate is 100%, and then pre-baking at 80° C. for 2 min and baking at 110° C. for 4 min to obtain the wear-resistant chenille yarn;
[0030] The modified polyester is prepared by the following steps:
[0031] Step A1: 2-allylcyclohexanone, m-chloroperbenzoic acid and dichloromethane were mixed, and the mixture was reacted for 24 hours at room temperature at a stirring rate of 240 rpm to obtain an intermediate M. Commercially available Deco Island Gold CNT204 hydroxylated carbon nanotubes, intermediate M and caprolactone were mixed and ultrasonically dispersed for 20 minutes, and then stirred and stannous isooctanoate was added under nitrogen protection at a stirring rate of 600 rpm and a temperature of 110°C, and the mixture was reacted for 24 hours to obtain modified carbon nanotubes.
[0032] The ratio of 2-allylcyclohexanone to m-chloroperbenzoic acid is 0.03 mol:0.05 mol, and the ratio of hydroxylated carbon nanotubes, intermediate M and caprolactone is 0.9 g:0.03 mol:0.08 mol;
[0033] Step A2: terephthalic acid, ethylene glycol, antimony trioxide and triphenyl phosphate were mixed, and the mixture was reacted for 2 h under nitrogen protection, at a stirring rate of 500 rpm and a temperature of 220° C., and then pentaerythritol was added and the temperature was raised to 270° C., the system pressure was maintained at -0.09 MPa, and the reaction was continued for 1 h. Then, modified carbon nanotubes and pyromellitic anhydride were added, and the reaction was continued for 1 h to obtain a modified polyester;
[0034] The amount ratio of terephthalic acid, ethylene glycol, antimony trioxide, triphenyl phosphate, pentaerythritol, modified carbon nanotubes and pyromellitic anhydride is 0.9 mol: 1.5 mol: 0.09 g: 0.1 g: 0.015 mol: 3 g: 0.015 mol;
[0035] The modified finishing agent is prepared by the following steps:
[0036] Step B1: Mix cyanuric chloride and acetone, stir at a stirring rate of 240 rpm, and add p-nitrophenol and potassium hydroxide solution, and react for 2 hours to obtain intermediate a; mix 3-aminopropyltriethoxysilane, intermediate a and acetone, add saturated sodium carbonate solution to adjust the pH value to 9, and react for 6 hours under nitrogen protection, stirring at a rate of 240 rpm, and a temperature of 80°C to obtain intermediate b; mix intermediate b, palladium carbon catalyst and ethanol, and introduce hydrogen, and react for 8 hours at a stirring rate of 100 rpm and a temperature of 50°C to obtain intermediate c;
[0037] The molar concentration of potassium hydroxide solution is 1 mol / L, the amount ratio of cyanuric chloride, p-nitrophenol and potassium hydroxide solution is 0.05 mol: 0.05 mol: 50 mL, the amount ratio of 3-aminopropyltriethoxysilane and intermediate a is 0.1 mol: 0.05 mol, and the amount ratio of intermediate b and palladium carbon catalyst is 0.05 mol: 0.8 g;
[0038] Step B2: 10-(2,5-dihydroxyphenyl)-10H-9-oxa-10-phosphaphenanthrene-10-oxide, epichlorohydrin, dichloromethane and deionized water were mixed, stirred at a stirring rate of 240 rpm and a temperature of 50°C, and sodium hydroxide was added to react for 8 hours to obtain intermediate d. Intermediate c, intermediate d and anhydrous ethanol were mixed, stirred at a stirring rate of 400 rpm and room temperature for 1 hour to obtain intermediate e;
[0039] The ratio of 10-(2,5-dihydroxyphenyl)-10H-9-oxa-10-phosphaphenanthrene-10-oxide, epichlorohydrin and sodium hydroxide is 0.01 mol: 0.02 mol: 4 g, and the ratio of intermediate c to intermediate d is 0.05 mol: 0.02 mol;
[0040] Step B3: The intermediate e, lipoic acid and dichloromethane were mixed, and 1-ethyl-(3-dimethylaminopropyl)carbodiimide, 4-dimethylaminopyridine and triethylamine were added under stirring at a rate of 200 rpm and room temperature in a dark environment, and the mixture was reacted for 24 hours to obtain a modified finishing agent;
[0041] The amount ratio of intermediate e, thioctic acid, 1-ethyl-(3-dimethylaminopropyl)carbodiimide, 4-dimethylaminopyridine and triethylamine is 0.02 mol: 0.05 mol: 0.08 mol: 0.08 mol: 0.12 mol.
[0042] Example 2 A wear-resistant chenille yarn is prepared by the following steps:
[0043] Step S1: adding the modified polyester to a melt spinning machine, melt spinning, and obtaining the modified polyester filaments, and passing through a chenille spinning machine, using two modified polyester filaments as core yarns and six modified polyester filaments as decorative yarns, and sandwiching the decorative yarns between the two core yarns and twisting them in a spiral shape to obtain chenille yarns;
[0044] Step S2: Mixing a modified finishing agent, ethanol and water to prepare a modified finishing solution, wherein the mass concentration of the modified finishing agent in the modified finishing solution is 6 g / L, and the volume ratio of ethanol to water is 5:1. The chenille yarn is finished by a two-immersion and two-rolling method, wherein the chenille yarn is immersed in the modified finishing solution, the temperature of the two immersions is 30° C., the immersion time is 1 h, the bath ratio is 1:20, the rolling rate is 100%, and then pre-baking at 80° C. for 2 min and baking at 110° C. for 4 min to obtain the wear-resistant chenille yarn;
[0045] The modified polyester is prepared by the following steps:
[0046] Step A1: 2-allylcyclohexanone, m-chloroperbenzoic acid and dichloromethane were mixed, and the mixture was reacted for 20 hours at room temperature at a stirring rate of 300 rpm to obtain an intermediate M. Commercially available Deco Island Gold CNT204 hydroxylated carbon nanotubes, intermediate M and caprolactone were mixed and ultrasonically dispersed for 20 minutes, and then stirred and stannous isooctanoate was added under nitrogen protection at a stirring rate of 700 rpm and a temperature of 110°C, and the mixture was reacted for 24 hours to obtain modified carbon nanotubes.
[0047] The ratio of 2-allylcyclohexanone to m-chloroperbenzoic acid is 0.04 mol:0.05 mol, and the ratio of hydroxylated carbon nanotubes, intermediate M and caprolactone is 0.9 g:0.04 mol:0.1 mol;
[0048] Step A2: terephthalic acid, ethylene glycol, antimony trioxide and triphenyl phosphate were mixed, and the mixture was reacted for 1.5 hours under nitrogen protection, a stirring rate of 600 rpm, and a temperature of 220° C., and then pentaerythritol was added and the temperature was raised to 270° C., the system pressure was maintained at -0.09 MPa, and the reaction was continued for 1 hour, and then modified carbon nanotubes and pyromellitic anhydride were added, and the reaction was continued for 1.5 hours to obtain a modified polyester;
[0049] The usage ratio of terephthalic acid, ethylene glycol, antimony trioxide, triphenyl phosphate, pentaerythritol, modified carbon nanotubes and pyromellitic anhydride is 1 mol: 1.8 mol: 0.1 g: 0.12 g: 0.02 mol: 3-4 g: 0.015 mol;
[0050] The modified finishing agent is prepared by the following steps:
[0051] Step B1: Mix cyanuric chloride and acetone, stir at a stirring rate of 300 rpm and a temperature of 5°C, add p-nitrophenol and potassium hydroxide solution, and react for 1 hour to obtain intermediate a; mix 3-aminopropyltriethoxysilane, intermediate a and acetone, add saturated sodium carbonate solution to adjust the pH value to 9, and react for 4 hours under nitrogen protection at a stirring rate of 300 rpm and a temperature of 80°C to obtain intermediate b; mix intermediate b, palladium carbon catalyst and ethanol, and introduce hydrogen, and react for 6 hours at a stirring rate of 120 rpm and a temperature of 50°C to obtain intermediate c;
[0052] The molar concentration of potassium hydroxide solution is 1 mol / L, the amount ratio of cyanuric chloride, p-nitrophenol and potassium hydroxide solution is 0.05 mol: 0.055 mol: 50 mL, the amount ratio of 3-aminopropyltriethoxysilane and intermediate a is 0.1 mol: 0.05 mol, and the amount ratio of intermediate b and palladium carbon catalyst is 0.05 mol: 1 g;
[0053] Step B2: 10-(2,5-dihydroxyphenyl)-10H-9-oxa-10-phosphaphenanthrene-10-oxide, epichlorohydrin, dichloromethane and deionized water are mixed, stirred at a stirring rate of 240-300 rpm and a temperature of 50° C., and sodium hydroxide is added to react for 8-10 hours to obtain intermediate d. Intermediate c, intermediate d and anhydrous ethanol are mixed, and the reaction is carried out at a stirring rate of 400-500 rpm and room temperature for 0.5-1 hour to obtain intermediate e;
[0054] The ratio of 10-(2,5-dihydroxyphenyl)-10H-9-oxa-10-phosphaphenanthrene-10-oxide, epichlorohydrin and sodium hydroxide is 0.01 mol: 0.024 mol: 4 g, and the ratio of intermediate c to intermediate d is 0.05 mol: 0.02 mol;
[0055] Step B3: Intermediate e, lipoic acid and dichloromethane were mixed, stirred at a rate of 240 rpm and room temperature in a dark environment, and 1-ethyl-(3-dimethylaminopropyl)carbodiimide, 4-dimethylaminopyridine and triethylamine were added, and the mixture was reacted for 24 hours to obtain a modified finishing agent;
[0056] The usage ratio of intermediate e, thioctic acid, 1-ethyl-(3-dimethylaminopropyl)carbodiimide, 4-dimethylaminopyridine and triethylamine is 0.03 mol: 0.06 mol: 0.08 mol: 0.08 mol: 0.12 mol.
[0057] Example 3 A wear-resistant chenille yarn is prepared by the following steps:
[0058] Step S1: adding the modified polyester to a melt spinning machine, melt spinning, and obtaining the modified polyester filaments, and passing through a chenille spinning machine, using two modified polyester filaments as core yarns and six modified polyester filaments as decorative yarns, and sandwiching the decorative yarns between the two core yarns and twisting them in a spiral shape to obtain chenille yarns;
[0059] Step S2: Mixing a modified finishing agent, ethanol and water to prepare a modified finishing liquid, wherein the mass concentration of the modified finishing agent in the modified finishing liquid is 8 g / L, and the volume ratio of ethanol to water is 5:1. The chenille yarn is finished by a two-immersion and two-rolling method, wherein the chenille yarn is immersed in the modified finishing liquid, the temperature of the two immersions is 30° C., the immersion time is 1 h, the bath ratio is 1:20, the rolling rate is 100%, and then pre-baking at 80° C. for 2 min and baking at 110° C. for 4 min to obtain the wear-resistant chenille yarn;
[0060] The modified polyester is prepared by the following steps:
[0061] Step A1: 2-allylcyclohexanone, m-chloroperbenzoic acid and dichloromethane were mixed, and the mixture was reacted for 24 hours at room temperature at a stirring rate of 300 rpm to obtain an intermediate M. Commercially available Deco Island Gold CNT204 hydroxylated carbon nanotubes, intermediate M and caprolactone were mixed and ultrasonically dispersed for 20 minutes, and then stirred and stannous isooctanoate was added under nitrogen protection at a stirring rate of 700 rpm and a temperature of 110°C, and the mixture was reacted for 24 hours to obtain modified carbon nanotubes.
[0062] The ratio of 2-allylcyclohexanone to m-chloroperbenzoic acid is 0.04 mol:0.06 mol, and the ratio of hydroxylated carbon nanotubes, intermediate M and caprolactone is 1 g:0.04 mol:0.1 mol;
[0063] Step A2: terephthalic acid, ethylene glycol, antimony trioxide and triphenyl phosphate were mixed, and the mixture was reacted for 2 h under nitrogen protection, with a stirring rate of 600 rpm and a temperature of 220° C., and then pentaerythritol was added and the temperature was raised to 270° C., and the system pressure was maintained at -0.09 MPa, and the reaction was continued for 1 h. Then, modified carbon nanotubes and pyromellitic anhydride were added, and the reaction was continued for 1.5 h to obtain a modified polyester;
[0064] The usage ratio of terephthalic acid, ethylene glycol, antimony trioxide, triphenyl phosphate, pentaerythritol, modified carbon nanotubes and pyromellitic anhydride is 1 mol: 1.8 mol: 0.1 g: 0.12 g: 0.02 mol: 4 g: 0.02 mol;
[0065] The modified finishing agent is prepared by the following steps:
[0066] Step B1: Mix cyanuric chloride and acetone, stir at a stirring rate of 300 rpm and a temperature of 5°C, add p-nitrophenol and potassium hydroxide solution, and react for 2 hours to obtain intermediate a; mix 3-aminopropyltriethoxysilane, intermediate a and acetone, add saturated sodium carbonate solution to adjust the pH value to 9, and react for 6 hours under nitrogen protection at a stirring rate of 300 rpm and a temperature of 80°C to obtain intermediate b; mix intermediate b, palladium carbon catalyst and ethanol, and introduce hydrogen, and react for 8 hours at a stirring rate of 120 rpm and a temperature of 50°C to obtain intermediate c;
[0067] The molar concentration of potassium hydroxide solution is 1 mol / L, the amount ratio of cyanuric chloride, p-nitrophenol and potassium hydroxide solution is 0.05 mol: 0.055 mol: 60 mL, the amount ratio of 3-aminopropyltriethoxysilane and intermediate a is 0.12 mol: 0.05 mol, and the amount ratio of intermediate b and palladium carbon catalyst is 0.05 mol: 1 g;
[0068] Step B2: 10-(2,5-dihydroxyphenyl)-10H-9-oxa-10-phosphaphenanthrene-10-oxide, epichlorohydrin, dichloromethane and deionized water were mixed, stirred at a stirring rate of 300 rpm and a temperature of 50°C, and sodium hydroxide was added to react for 10 hours to obtain intermediate d. Intermediate c, intermediate d and anhydrous ethanol were mixed, stirred at a stirring rate of 500 rpm and room temperature for 1 hour to obtain intermediate e;
[0069] The ratio of 10-(2,5-dihydroxyphenyl)-10H-9-oxa-10-phosphaphenanthrene-10-oxide, epichlorohydrin and sodium hydroxide is 0.01 mol: 0.024 mol: 5 g, and the ratio of intermediate c to intermediate d is 0.05 mol: 0.03 mol;
[0070] Step B3: Intermediate e, lipoic acid and dichloromethane were mixed, stirred at a rate of 240 rpm and room temperature in a dark environment, and 1-ethyl-(3-dimethylaminopropyl)carbodiimide, 4-dimethylaminopyridine and triethylamine were added, and the mixture was reacted for 24 hours to obtain a modified finishing agent;
[0071] The usage ratio of intermediate e, thioctic acid, 1-ethyl-(3-dimethylaminopropyl)carbodiimide, 4-dimethylaminopyridine and triethylamine is 0.03 mol: 0.06 mol: 0.08 mol: 0.08 mol: 0.12 mol.
[0072] Comparative Example 1 Compared with Example 3, this comparative example is different in that the intermediate M in Example 3 during the preparation of the modified polyester in Example 3 is replaced with caprolactone, and the other steps are the same.
[0073] Comparative Example 2 Compared with Example 3, this comparative example removes pentaerythritol and pyromellitic anhydride in the preparation process of the modified polyester in Example 3, and the other steps are the same.
[0074] Comparative Example 3 Compared with Example 3, this comparative example is different in that the intermediate d in the preparation process of the modified finishing agent in Example 3 is replaced by resorcinol diglycidyl ether, and the other steps are the same.
[0075] Comparative Example 4 Compared with Example 3, this comparative example is different in that 3-aminopropyltriethoxysilane in the preparation process of the modified finishing agent in Example 3 is replaced by propylamine, and the other steps are the same.
[0076] Take the wear-resistant chenille yarns prepared in Example 1, Example 2, Example 3, Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4, refer to GB / T14344-2022, measure the breaking strength of the wear-resistant chenille yarn, the clamping distance is 250 mm, the tensile speed is 200 mm / min, refer to FZ / T01058-1999, use a reciprocating wear tester to test the wear-resistant chenille yarn, the tension weight used is 35 g, the water sandpaper is 400, and the number of frictions when it breaks is recorded. Refer to GB / T 5454-1997, test the limiting oxygen index of the wear-resistant chenille yarn, wash the wear-resistant chenille yarn 50 times under the same conditions, and measure the number of breaks and the limiting oxygen index after washing again. The test results are shown in Table 1:
[0077] Table 1
[0078] Test items Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Breaking strength (cN / Tex) 12.12 12.14 12.19 12.17 10.48 12.18 12.19 Number of fractures (times) 657 654 668 597 534 662 484 Limiting oxygen index (%) 28.29 28.32 28.36 28.29 28.18 26.48 27.64 Number of breaks after washing (times) 622 619 633 447 499 615 401 Limiting oxygen index after washing (%) 27.85 27.88 27.94 24.14 27.37 25.97 23.81
[0079] It can be seen from the test results in the table shown that when Example 7, Example 8 and Example 9 are compared with Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4, in Comparative Example 1, the intermediate M in Example 3 in the preparation process of the modified polyester in Example 3 is replaced with caprolactone, and the number of breakages decreases, and the performance after washing decreases significantly, indicating that the covalent bond connection between the modified finishing agent and the modified polyester filament can effectively improve the wear resistance and water washing resistance of the chenille yarn. In Comparative Example 2, pentaerythritol and pyromellitic anhydride in the preparation process of the modified polyester in Example 3 are removed. Due to the modified polyester The ester lacks a branched structure and cannot be connected to the modified carbon nanotubes by covalent bonds, resulting in a significant decrease in the breaking strength of the wear-resistant chenille yarn. In Comparative Example 3, the intermediate d in the preparation process of the modified finishing agent in Example 3 is replaced with resorcinol diglycidyl ether. Due to the lack of DOPO flame retardant groups, the flame retardant properties of the wear-resistant chenille yarn are significantly reduced. In Comparative Example 4, the 3-aminopropyltriethoxysilane in the preparation process of the modified finishing agent in Example 3 is replaced with propylamine. Due to the lack of a cross-linked network formed after the hydrolysis of the silylethoxy group, its various properties are reduced to a certain extent.
[0080] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0081] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.
Claims
1. A production process for wear-resistant chenille yarn, characterized in that: The method is as follows: Step S1: adding modified polyester to a melt spinning machine, melt spinning, and obtaining modified polyester filaments; passing through a chenille spinning machine, using two modified polyester filaments as core yarns and six modified polyester filaments as decorative yarns, and sandwiching the decorative yarns between the two core yarns and twisting them in a spiral shape to obtain chenille yarns; Step S2: Mixing a modified finishing agent, ethanol and water to prepare a modified finishing liquid, wherein the mass concentration of the modified finishing agent in the modified finishing liquid is 4-8 g / L, and the volume ratio of ethanol to water is 5:
1. The chenille yarn is finished by a two-immersion and two-rolling method, wherein the chenille yarn is immersed in the modified finishing liquid, the temperature of the two immersions is 30° C., the immersion time is 1 h, the bath ratio is 1:20, the rolling rate is 100%, and then pre-baking at 80° C. for 2 min and baking at 110° C. for 4 min to obtain the wear-resistant chenille yarn; The modified polyester is prepared by the following steps: Step A1: 2-allylcyclohexanone, m-chloroperbenzoic acid and dichloromethane are mixed, and the mixture is reacted for 20-24 hours at room temperature at a stirring rate of 240-300 rpm to obtain an intermediate M. The hydroxylated carbon nanotubes, the intermediate M and caprolactone are mixed and ultrasonically dispersed for 20 minutes, and then, under nitrogen protection, the stirring rate is 600-700 rpm, and the temperature is 110° C., stannous isooctanoate is added, and the mixture is reacted for 24 hours to obtain a modified carbon nanotube; Step A2: terephthalic acid, ethylene glycol, antimony trioxide and triphenyl phosphate are mixed, and the mixture is reacted for 1.5-2h under nitrogen protection, at a stirring rate of 500-600rpm and a temperature of 220°C. Pentaerythritol is then added and the temperature is raised to 270°C, the system pressure is maintained at -0.09Mpa, the reaction is carried out for 1h, and then modified carbon nanotubes and pyromellitic anhydride are added, and the reaction is continued for 1-1.5h to obtain a modified polyester.
2. The production process of a wear-resistant chenille yarn according to claim 1, characterized in that: In step A1, the ratio of 2-allylcyclohexanone to m-chloroperbenzoic acid is 0.03-0.04 mol: 0.05-0.06 mol, and the ratio of hydroxylated carbon nanotubes, intermediate M and caprolactone is 0.9-1 g: 0.03-0.04 mol: 0.08-0.1 mol.
3. The production process of a wear-resistant chenille yarn according to claim 1, characterized in that: In step A2, the amount ratio of terephthalic acid, ethylene glycol, antimony trioxide, triphenyl phosphate, pentaerythritol, modified carbon nanotubes and pyromellitic anhydride is 0.9-1 mol: 1.5-1.8mol: 0.09-0.1g: 0.1-0.12g: 0.015-0.02mol: 3-4g: 0.015-0.02mol.
4. The production process of a wear-resistant chenille yarn according to claim 1, characterized in that: The modified finishing agent is prepared by the following steps: Step B1: Mix cyanuric chloride and acetone, stir at a rate of 240-300 rpm, and add p-nitrophenol and potassium hydroxide solution, and react for 1-2 hours to obtain intermediate a; mix 3-aminopropyltriethoxysilane, intermediate a and acetone, add saturated sodium carbonate solution to adjust the pH value to 9, and react for 4-6 hours under nitrogen protection, stirring at a rate of 240-300 rpm, and a temperature of 80°C to obtain intermediate b; mix intermediate b, palladium carbon catalyst and ethanol, and introduce hydrogen, and react for 6-8 hours at a stirring rate of 100-120 rpm and a temperature of 50°C to obtain intermediate c; Step B2: 10-(2,5-dihydroxyphenyl)-10H-9-oxa-10-phosphaphenanthrene-10-oxide, epichlorohydrin, dichloromethane and deionized water are mixed, stirred at a stirring rate of 240-300 rpm and a temperature of 50° C., and sodium hydroxide is added to react for 8-10 hours to obtain intermediate d. Intermediate c, intermediate d and anhydrous ethanol are mixed, and the reaction is carried out at a stirring rate of 400-500 rpm and room temperature for 0.5-1 hour to obtain intermediate e; Step B3: Intermediate e, lipoic acid and dichloromethane were mixed, stirred at a rate of 200-240 rpm and room temperature in a dark environment, and 1-ethyl-(3-dimethylaminopropyl)carbodiimide, 4-dimethylaminopyridine and triethylamine were added, and the mixture was reacted for 24 hours to obtain a modified finishing agent.
5. The production process of a wear-resistant chenille yarn according to claim 4, characterized in that: In step B1: the molar concentration of potassium hydroxide solution is 1 mol / L, the amount ratio of cyanuric chloride, p-nitrophenol and potassium hydroxide solution is 0.05 mol: 0.05-0.055 mol: 50-60 mL, the amount ratio of 3-aminopropyltriethoxysilane and intermediate a is 0.1-0.12 mol: 0.05 mol, and the amount ratio of intermediate b and palladium carbon catalyst is 0.05 mol: 0.8-1 g.
6. The production process of a wear-resistant chenille yarn according to claim 4, characterized in that: In step B2: the ratio of 10-(2,5-dihydroxyphenyl)-10H-9-oxa-10-phosphaphenanthrene-10-oxide, epichlorohydrin and sodium hydroxide is 0.01 mol: 0.02-0.024 mol: 4-5 g, and the ratio of intermediate c to intermediate d is 0.05 mol: 0.02-0.03 mol.
7. The production process of a wear-resistant chenille yarn according to claim 4, characterized in that: In step B3, the ratio of the intermediate e, thioctic acid, 1-ethyl-(3-dimethylaminopropyl)carbodiimide, 4-dimethylaminopyridine and triethylamine is 0.02-0.03 mol: 0.05-0.06 mol: 0.08 mol: 0.08 mol: 0.12 mol.
8. A wear-resistant chenille yarn, characterized in that: Prepared according to any one of the production processes described in claims 1-7.
Citation Information
Patent Citations
Core-spun yarn and production method thereof
CN109355911A
Heating chenille yarn and preparation process thereof
CN117802657A
Cited By
Antibacterial chenille yarn and production process thereof
CN120520002A